(Re-)claiming bodies through fashion and style: gendered configurations in Muslim contexts - Thimm, Viola (Springer International Publishing, 2021)
Chapter 1: Introduction: (Re-)Claiming Bodies through Fashion and Style. Gendered Configurations in Muslim Contexts (Viola Thimm) -- Part I: Modesty and Fashion: Reconfiguring Social Conditions & Identifications -- Chapter 2: Beauty East, Beauty West: Muslim Beauty in Indonesian Islamic Magazines (Diah Ariani Arimbi) -- Chapter 3: “We create with our bodies an individual stage to share our Iman and beauty with the world.” Practices of clothing and embodiment as identification markers among Muslims in Germany (Sabine Damir–Geilsdorf, Yasmina Shamdin) -- Chapter 4: How I wear my headscarf. Narratives from young Danish Muslim women in Copenhagen (Gülzar Demir, Marie–Louise Nosch and Else Skjold) -- Chapter 5: Modest Fashion and the Discourse on Intersectional Diversity (Laura Haddad) -- Chapter 6: Men’s Non-Fashion: Embodying Traditionality in the Gulf -- Part II: Normative Orders, Subjectivation and Counteractive Practices (Viola Thimm) -- Chapter 7: The Halal Nail Polish: Religion and Body Politics in the Marketplace (Özlem Sandıkcı) -- Chapter 8: Hijab as Migration: Embracing and Leaving Hijab in Contemporary Indonesia (Yulianingsih Riswan) -- Chapter 9: After the hijab: Liminal states of post-veiling embodiment (Alicia Izharuddin) -- Chapter 10: High heels and Rainbow Hijabs: Reclaiming the Islamic LGBTQ bodies through fashion innovations (Nancy Pathak) -- Part III: Materiality, Political Discourses, and Power -- Chapter 11: The fabric of diasporic designs: wearing Panjabi suits home & away among South Asian women in Europe (Sara Bonfanti) -- Chapter 12: The Materiality and Social Agency of the Malaḥfa (Mauritanian Veil) (Katherine Ann Wiley) -- Chapter 13: More than a Garment: The Haīk in Morocco and Algeria as a Means of Feminist Artistic Expression and Decolonial Self-Empowerment (Isabella Schwaderer) -- Chapter 14: The female body as subject of the Discourse of Power (Rhea Maria Dehn Tutosaus).